Virtual learning environments and research competences in peruvian basic education teachers of Tacna city - Catacora Lopez, Eliseo (2024)
This article contributes to establish the virtual learning environments influence in the development of research competencies in the elementary and secondary teachers in Peruvian Basic Education of Tacna city. We choose a mixed methodology; the sample were 70 teachers who we took a survey to measure the virtual environments dimensions and an interview to measure the research competences dimensions. The results showed that a high percentage of the teachers used to use the virtual learning environment “Peru Educa platform” but a large majority didn’t use the steps to carry out research work. In addition, they did not elaborate educative materials in collaborative work platforms not even used reliable bibliographic references